A multidisciplinary‐led early arthritis service to manage client‐identified participation restrictions in early inflammatory arthritis: A qualitative study of service user and staff perspectives. (7th August 2022) - Codd, Yvonne; Coe, Áine; Kane, David; Mullan, Ronan H.; Stapleton, Tadhg
Abstract: Background: The impact of inflammatory arthritis (IA) on occupational performance and on participation in meaningful life roles is recognised. However, limited research has explored how clinical services support broader life impact and participation restrictions associated with early disease as part of routine healthcare. This exploratory study was undertaken to describe how a novel multidisciplinary‐led early arthritis service approach addresses client‐identified participation restrictions in early IA. Methods: Qualitative Description (QD) approaches were used to explore perspectives of staff and clients of these multidisciplinary‐led early arthritis services in Ireland. Data were gathered using focus groups with staff, and individual semi‐structured interviews with clients. Transcripts were analysed using thematic analysis. Results: Fifteen staff working in these services participated in the focus groups and 43 clients with IA participated in interviews (female n = 31); diagnosis duration ranged from 5 to 24 months. Participants described how the multidisciplinary‐led service had a clear remit to address participation alongside traditional symptom management and provided automatic, immediate access to interventions focussed on identification and management of participation restrictions experienced in early disease. The service model utilised a delivery approach that allowed for ease of early access to a full multidisciplinary team and prolonged support. The most significant feature of the service approach was 'the centrality of the client' which influenced a person‐centred approach to identification of needs and priorities for interventions. Conclusion: Findings indicate the role and value of this innovative multidisciplinary approach in addressing client‐identified participation restrictions in routine clinical practice that is positively regarded by clients and staff.